Techniques Used in the Content of Tiktok Videos as English Learning Media - Betharia Sembiring Pandia; Berlin Sibarani (ITScience (Information Technology and Science), 2024)
Social media have reached a pivotal role in human’s daily lives; it can be a source of information and even a source of learning in the educational field. This study explores the techniques of content creators who use social media to provide engaging language learning materials to social media users. This study uses a descriptive qualitative method. The data source is the os on the social media platform TikTok. This short-form video-sharing media study has two groups: high followers, as many as four accounts, and low followers, as many as nine accounts. There are 20 videos from each group. Each video is identified based on the theory of language teaching techniques. Then, the methods used by high and low followers are identified and described. This study found that the creators with high followers use communicative language teaching methods, precisely information gap and feedback type. Meanwhile, the creators with low followers base their content on a direct teaching method in which they tend to explain and give lectures to their audience. Hence, this finding is expected to be useful for English teachers, particularly in terms of adapting techniques to teach English in real-world language usage and idiomatic expressions often absent in traditional textbooks.